Silage characteristics and preference of sheep for wet brewer's grain ensiled with maize cob (2015)
In order to meet the shortfall in feed supply and provide adequate nutrition for sheep during the dry season, wet brewer’s grain (WBG) was ensiled with 0, 10, 20, and 30 % of crushed maize cob (MC). The physical characteristics, pH and chemical composition of the silage mixtures were determined at 21 days of ensiling. Acceptability and preference of sheep among the silage mixtures were determined in a cafeteria feeding trial using eighteen West African dwarf (WAD) sheep. The experimental design adopted was the completely randomized design. The colour, smell and texture of the mixtures showed that all silages had acceptable physical attributes. The pH of silage varied from 3.40 - 3.80, indicating that the silage mixtures were adequately fermented. Silage scores however revealed that the best physical attributes were attained at 20 % inclusion of maize cob to WBG. Dry matter (DM) content of silage was 26.88, 31.44, 36.69, 43.50% while crude protein (CP) content was 23.44, 19.11, 14.00, and 12.00% for silage with 0, 10, 20 and 30% of maize cob respectively. Neutral detergent fibre increased from 40.33 - 62.67 % and acid detergent from 25.00 - 39.67% with increasing level of maize cob in the mixture. The coefficient of preference (CoP) and percent preference showed that WBG silage with 10% MC was more acceptable and preferred by sheep than other silage mixtures. While physical attributes of silage showed that the optimum level of MC inclusion was 20%, animal preference indicate that this level was less acceptable to sheep. Sheep may require more time to adapt to higher levels of MC in the silage mixture.